Pengaruh Variabel Makro Ekonomi Terhadap Nilai Aktiva Bersih Reksa Dana Syariah di Indonesia Tahun 2018-2024 - Alif Amru Ramadhan; Siti Fatimah Nurhayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Net Asset Value (NAV) of sharia mutual funds is an indicator of sharia mutual fund growth. This study analyzes the influence of macroeconomic variables, namely inflation, exchange rates, Bank Indonesia interest rates (BI rate), and money supply, on the Net Asset Value (NAV) of sharia mutual funds in Indonesia from January 2018 to September 2024. This study uses time series data and the Partial Adjustment Model (PAM) method in multiple linear regression analysis. The selection of PAM is based on the assumption that the adjustment of NAV to changes in macroeconomic variables is gradual towards long-term equilibrium. The results show that inflation, exchange rates, and money supply significantly affect the NAV of sharia mutual funds. Inflation and exchange rates show a negative influence, while the money supply has a positive influence. Exchange rate stability and controlled inflation are crucial for NAV growth. Conversely, increased liquidity, indicated by a larger money supply, can stimulate investment in sharia mutual funds. The BI rate does not show a significant influence on NAV influence investment decisions in the sharia capital market. These findings have important implications for regulators and market players to maintain macroeconomic stability to support the sustainable growth of the sharia mutual fund sector in Indonesia.